Produção e caracterização de redes de Bragg gravadas em fibra multimodo e aplicadas ao setor de biocombustíveis - Corotti, Raquel de Paiva (2015)
In this work, a multimode fiber Bragg refractive sensor for the liquid fuel sector is described. The use of etched devices is proposed to overcome the drawbacks associated with sensing high refractive index samples employing fiber transducers. The transducer sensitivity can be tailored by adjusting the final diameter of the etched Bragg grating. Due to a trade between the signal-to-noise ratio and the sensitivity, operational parameters of the sensor must be designed to match the expected refractive index dynamic range for specific applications. Metrological properties of the sensor are determined, resulting in resolution from 5.6% v/v to 0.4% v/v for refractive indexes ranging from 1.4562 to 1.4729. Specific applications regarding the quality assessment of biodiesel and conformity analysis of diesel- biodiesel blends are discussed.